FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPATUHAN PASIEN TERHADAP PENGOBATAN TUBERKULOSIS PARU DI LIMA PUSKESMAS SE-KOTA PEKANBARU - Adelia Ratna Sundari Gunawan; Rohani Lasmaria Simbolon; Dina Fauzia (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTTuberculosis (TB) disease is a transmitted infection that caused by Mycobacterium Tuberculosis (M. Tuberculosis). In 2015, Indonesia is in the 2nd place after Tiongkok in the world and the case of TB in Indonesia increases twice from the previous year which is about 1 million new cases per year. The success full of a program is determined by the patients’ obedient in consuming medicine completely therefore of effective intervention increasing the early initiation, obedience and completion the treatment of TB are required. There are five healt centers that have the most TB cases in Pekanbaru namely Puskesmas Sidomulyo which is 68 cases, Rejosari which is 64 cases, Payung Sekaki which is 60 cases, Simpang Tiga Which is 56 cases and Garuda which is 48 cases. The patients can be cured if they are discipline in following the treatment of TB, comply the schedule of the treatment regularly, the functionary visits the patients regularly and the good role of the family. This research is aimed to find out the factors affecting the patients’ obedient in TB treatment. The research was conducted in each patients’house with TB by using descriptive method and cross sectional approach. The sample of this research was 75 patients and 20 patients are for the validity and reliability test. The most patients are in 45 years old (36%), the male patients (64%), the average of the patients’house distance is > 2 Km which is 77,3%, patients who have motorcycle (96,1%), patients’ income < 1 million (38,7%), the last education of the patient is Sekolah Menengah Atas (SMA)/ Madrasah Aliyah (MA)/Equivalent (58,7%), good knowledge (86,7%), good attitude (85,3%), good motivation (100%), the avaibility of good medicine (100%), the average patients in the intensive stage of category 1 month -2 (22,7%), the good role of Pengawas Menelan Obat (PMO) (85,3%), and the good support from family (88%). There are tree factors affecting the patients’ obedient on the TB treatment in five Healt Centers in Pekanbaru namely motivation to be cured, the role of family and the role of PMO.Keywords : Tuberculosis, TB treatment, the role of PMO, the role of family.